2016
DOI: 10.1002/marc.201600250
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chiral Oligomer‐Grafted Biodegradable Polyurethanes and Their Chiral‐Dependent Influence on Bone Marrow Stem Cell Behaviors

Abstract: Chirality is one of the most fascinating and ubiquitous features in nature, especially in biological systems. The effects of chiral surfaces, especially in combination with degradable materials of good biocompatibility, on stem cell behaviors has not yet been tackled. In this communication, the chiral monomers N-acryloyl-l(d)-valine (l(d)-AV) are synthesized and are polymerized to obtain chiral (l(d)-PAV-SH) oligomers, which are covalently immobilized onto electron-deficient poly(propylene fumarate) polyuretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The N ‐acryloyl‐ l ( d )‐valine chiral monomers are produced and polymerized to get chiral ( l ( d )‐PAV‐SH) oligomers, and covalently immobilized on electron‐deficient poly(propylene fumarate)‐based polyurethane (PPFU). The PPFU‐ l ‐PAV associates strongly and effectively with bone marrow stem cells (BMSCs) than the PPFU‐ d ‐PAV, resulting in a larger area of cell distribution, a higher velocity of migration and a stronger propensity for osteo‐differentiation 10 . The interaction of l ‐poly(acryloyl‐valine) ( l ‐PAV) and d ‐poly(acryloyl‐valine) ( d ‐PAV) chiral brushes with gold nanoparticles (NPs), nanooctahedras (NOs) and nano cubes (NCs) have been studied to investigate the albumin protein adsorption, 11 mesenchymal cell differentiation, 12 cellular uptake and cytotoxicity in A549 and HepG2 cells 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N ‐acryloyl‐ l ( d )‐valine chiral monomers are produced and polymerized to get chiral ( l ( d )‐PAV‐SH) oligomers, and covalently immobilized on electron‐deficient poly(propylene fumarate)‐based polyurethane (PPFU). The PPFU‐ l ‐PAV associates strongly and effectively with bone marrow stem cells (BMSCs) than the PPFU‐ d ‐PAV, resulting in a larger area of cell distribution, a higher velocity of migration and a stronger propensity for osteo‐differentiation 10 . The interaction of l ‐poly(acryloyl‐valine) ( l ‐PAV) and d ‐poly(acryloyl‐valine) ( d ‐PAV) chiral brushes with gold nanoparticles (NPs), nanooctahedras (NOs) and nano cubes (NCs) have been studied to investigate the albumin protein adsorption, 11 mesenchymal cell differentiation, 12 cellular uptake and cytotoxicity in A549 and HepG2 cells 11 …”
Section: Introductionmentioning
confidence: 99%
“…The PPFU-L-PAV associates strongly and effectively with bone marrow stem cells (BMSCs) than the PPFU-D-PAV, resulting in a larger area of cell distribution, a higher velocity of migration and a stronger propensity for osteo-differentiation. 10 The interaction of L-poly(acryloylvaline) (L-PAV) and D-poly(acryloyl-valine) (D-PAV) chiral brushes with gold nanoparticles (NPs), nanooctahedras (NOs) and nano cubes (NCs) have been studied to investigate the albumin protein adsorption, 11 mesenchymal cell differentiation, 12 cellular uptake and cytotoxicity in A549 and HepG2 cells. 11 The immune system can differentiate between selfantigens and non-self-antigens to maintain the homeostasis in the body.…”
Section: Introductionmentioning
confidence: 99%
“…The above results revealed that the amino type could influence the chiral effects on biological systems. Our previous works also prepared chiral surface based on the valine and studied stereoselective interactions between cells and chiral interface materials [ 13 , 20 , 23 , 56 ]. We observed that cancer cells (e.g., A549 cells and HepG2 cells) prefer to internalize the d -PAV-AuNPs through the possible preferable interaction between the l -phospholipid-based cell membrane and the d -enantiomers [ 42 ], while the bone marrow mesenchymal stem cells uptake more l -PAV-AuNPs than the d -PAV coated ones [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] Chiral supramolecular polyurethanes with ordered hard segments and helical conformation have been further fabricated, which combines the respective advantages of helical polymers and elastomers. [31][32][33][34] Nakano et al reported the synthesis of a chiral polyurethane from optically active (R)−1,1′-bi(2-naphthol) (R-BINOL) and 1,4 phenylene diisocyanate. [32] While Hayes et al synthesized a series of novel supramolecular polyurethanes elastomers that feature chiral polar end-groups and investigated how highly oriented stereochemistry enhanced the phase separated structures and the mechanical properties of polyurethane.…”
Section: Introductionmentioning
confidence: 99%